Faktor-faktor yang mempengaruhi proses penghasilan karya dalam kalangan pengarca muda di Malaysia / Syed Alwi Syed Abu Bakar - Syed Alwi , Syed Abu Bakar (2017)
This research has completed to look on the factors that affect the process of sculpture fabrication among the young sculptors. The objective of this research is to find out the quality, the knowledge, the management and the productivity of the sculpture. The research obtain the data through the writing materials which is written by the past researchers and base on interviewed session with several young sculptors. Completing this research required a lot of analysing documents, observations and involving interviewing sculptors, these processes are suitable in the qualitative type of research. The research has taken about four years which it began with observation activities and then it will followed by interviewed and the analysing activities. The finding of this research shows the young sculptors need transformation in the process of producing of art works. The success of the transformation are based on the four factors that was stated earlier. The result has identified the young sculptors required their behaviour progression base on the four factors for establish their sculpture fabrication involving as an entreprenuecial activities. Thus, the research has the potential to benefit those who involved in the related field and they may use the finding to refer and upgrade their sculptures into a better expectation quality.